A study of the protein- and energy requirements of the pregnant gilt (sus scrofa domesticus) - Kemm, E. H.(Ernest Hercules) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D. (Agric.)) -- University of Stellenbosch, 1974.